THE PREVALENCE OF THYROID DISORDERS AMONG OVERWEIGHT AND OBESE PATIENTS IN A SINGLE-CENTRE - Bahrudin, Mohd Fyzal; Ng, Ooi Chuan (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Hypothyroidism can cause weight gain. While the prevalence of hypothyroidism among Malaysians is 2.1% (0.5% overt and 1.6% subclinical hypothyroidism), its prevalence among those who are overweight and obese is still unknown. METHODOLOGY This is a cross-sectional cohort study among participants of the Weight Loss Journey Program in Hospital Sultan Abdul Aziz Shah, University Putra Malaysia in March 2023. Overweight is defined as BMI ≥23.0 kg/m² and obese is defined as BMI ≥27.5 kg/m². Participants who agreed to do baseline blood exams were investigated for thyroid abnormalities. RESULT There were 151 participants in the weight loss challenge. The a mean age was 33 years old and majority were female (n = 124). The mean weight 80.9 kg (51.1-158.1 kg) with mean BMI of 31.6 kg/m² (23.0 – 57.5 kg/m²). A total of 72 participants consented to blood exam for serum thyroid stimulating hormone (TSH) and free thyroxine (T4) levels. The mean TSH was 1.39 uIU/mL (0.2- 3.49 uIU/mL), while the mean fT4 was 13.04 pmol/L (10.6-17.1 pmol/L). There were no participants with subclinical nor overt hypothyroidism. Paradoxically, there was a patient who had subclinical hyperthyroidism with TSH and T4 values of 0.2 uIU/mL and 15.5 pmol/L, respectively. CONCLUSION Subclinical or overt hypothyroidism did not seem to be an important cause of obesity locally. Hence, we recommend that thyroid function test only be required for those who have additional clinical features of thyroid disorder.